Analisis Proksimat Karbon Ampas Bengkuang (Pachyrhzus erosus) sebagai Sumber Material Maju - Fazhira Hanifah; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2023)
Jicama dregs contain starch which has the potential as a carbon source for advanced materials through the carbonization process to produce carbon. The purpose of this study was to determine the optimum carbonization temperature in order to obtain economical and quality jicama dregs carbon. Jicama dregs were carbonized at various temperatures of 250°C, 300°C, 350°C, 400°C and 450°C for 1 hour. The jicama dregs carbon was then analyzed proximately by testing the ash content, vapor content and bound carbon. The results showed that the optimal carbonization temperature was carbon produced at a temperature of 250°C with an ash content test of 28.92%, vapor content of 1.89% and bound carbon of 72.97%. The proximate analysis value almost meets the standard of SNI 06-3730-1995.